Factors Associated with Musculoskeletal Pain and Fatigue during Online Learning among Nursing Students - Butsripoom, Benjamaporn; Wittayapun, Yuwadee (Pacific Rim International Journal of Nursing Research, 2024)
Since the COVID-19 pandemic, nursing education has shifted to more online learning. This shift may cause some problems with musculoskeletal pain and fatigue. This cross-sectional study aimed to explore the incidence of musculoskeletal pain and fatigue and its associated factors in online learning among 234 undergraduate nursing students studied at one university in Bangkok, Thailand, from January to March 2023. The instruments included personal factors, Health Status, Online Learning Risks Assessment, the single-item Visual Analogue Scale (VAS) for fatigue, and Nordic Musculoskeletal Questionnaire. Chi-squared, t-test and logistic regression were used to analyze the data. Of the 234 respondents, 224 (94.9%) were women, averaging 20.6 ± 1.3 years old, and they spent an average of 7.5 hours per day on online work or study in chairs without backrests and armrests. About 86.8% spent three or more hours online, with over half (61.5%) using tablets as their main device and 33.3% using mobile phones. Over the past six months, 80.8% of participants had experienced musculoskeletal pain and 79.9% experienced moderate to severe fatigue. Sitting with the head down for over 2 hours daily was the strongest predictor for musculoskeletal pain, while sitting in the same spot for over two hours predicted fatigue. During online learning, musculoskeletal pain and fatigue can be prevented through targeted interventions that encourage regular breaks to reduce prolonged sitting and ergonomic adjustments for healthier sitting posture. The study recommends adding ergonomic and self-care education to nursing curricula to prevent discomfort from prolonged sitting and poor posture, especially in online learning.